Exploring Implicit Meta-Discourse In Legal Discourse: An Analysis Of The Chinese And American Constitutions - He, Mengyu; Rahim, Hajar Abdul (Universitas Pendidikan Indonesia, 2017)
Research in meta-discourse, particularly explicit meta-discourse or meta-discourse markers has contributed much knowledge on the discourse features of specialised genres. However, there are very few studies on implicit meta-discourse. The current study explores implicit meta-discourse in legal discourse by comparing the implicit interpersonal meta-discourse in the Constitution of the People’s Republic of China with the Constitution of the United States. The focus of the study is the use of implicit meta-discourse, particularly the grammatical meta-discourse in the legal discourse of two different languages and cultural groups. The findings demonstrate that there are similarities and differences in the use of implicit meta-discourse in the two constitutions. Within the context of language discourse, the findings of the current study suggest that legal discourse is distinctive in the use of implicit interpersonal meta-discourse, particularly in the way writers intrude into the discourse implicitly by certain key grammatical forms of meta-discourse. Despite the objectivity and rigour of legal discourse, the current study found that there is some level of subjectivity in such discourse, evident from the use of implicit meta-discourse.